Socio-geographic determinants of destroyed Serbian churches and monasteries in Kosovo and Metohija from 1999 to 2022 - Medojević, Jovo; Pavlović, Mila; Milosavljević, Saša (Sociološki pregled, 2023)
Throughout its spiritual, historical, and cultural life in the territory of Kosovo and Metohija, the Serbian Orthodox Church has shared fate with the Serbian people. In the past two decades, from 1999 to 2022, in addition to persecutions of the Serbian Orthodox population in Kosovo and Metohija by the local Albanians, we have also witnessed extensive destruction of Serbian cultural heritage, which is the research subject of this paper. With the application of the social and geographic research methodology, the aim of this paper is to gain scientific insight for the purpose of direct confirmation, substantiated by relevant documents, and presentation of all known cases of aggravated and substantial destruction, desecration, and vandalism of Serbian sacral heritage committed by members of the Albanian community in the territory of Kosovo and Metohija between 1999 and 2022.